The impact of sustainable supplier selection to supplier performance in mining industry: ethical culture as moderating variable - Nasar Buntu Laulita (Universitas Negeri Surabaya, 2021)
Sustainable supplier selection during tender is one of the critical factors in the supply chain management to maintain sustainable procurement in an organisation. Many factors contribute to the success of sustainable supplier selection practices, and ethical culture is one of the factors because it would influence supplier selection. This study aims to determine the effect of implementing sustainable supplier selection on supplier performance by moderating the effect of ethical culture in the mining industry. This type of research is explanatory research with hypothesis testing of 104 respondents by distributing questionnaires. The data analysis is conducted by Structural Equation Model (SEM). The research shows that the construct of sustainable supplier selection with economic, social, and environmental aspects as dimensions has a direct and significant impact on supplier performance in the mining industry. This research also shows that ethical culture has a significant moderating effect in the relationship between sustainable supplier selection and supplier performance. The managerial implication of this research is providing guideline for decision-makers to implement sustainable supplier selection by considering economic, social, and environmental aspects while maintaining an ethical culture as a part of work professionalism to maintain sustainable performance in the mining industry.